2022
DOI: 10.33448/rsd-v11i15.37663
|View full text |Cite
|
Sign up to set email alerts
|

Análise da Repercussão Cardiorrespiratória após COVID-19

Abstract: Introdução: A doença causada pelo novo coronavírus (COVID-19) é responsável por repercussões sistêmicas a médio e longo prazo. Fadiga e redução da aptidão cardiorrespiratória são sintomas frequentemente relatados. Objetivo: Avaliar a condição aeróbica de pacientes que foram infectados pelo SARS-COV-2 e as repercussões cardiorrespiratórias de acordo com a gravidade da doença. Métodos: Foram analisados os prontuários dos pacientes acometidos pela COVID-19 e submetidos ao teste cardiopulmonar de exercício (TCPE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Alongside with these symptoms, there is a growing concern about the cardiac complications experienced by these patients, with recent evidence showing a high prevalence of chest pain and arrhythmia 2 . Additionally, studies have not only found a significant decline in the aerobic condition of these individuals 3 but also identified an increased risk for chronotropic incompetence, a condition defined as an insufficient increase in heart rate to meet metabolic demands 4 . Such cardiac manifestations can lead to exercise intolerance, a deterioration in quality of life, and an increased risk of cardiovascular events and mortality, underscoring the need for a deeper understanding of cardiac involvement in long COVID.…”
mentioning
confidence: 99%
“…Alongside with these symptoms, there is a growing concern about the cardiac complications experienced by these patients, with recent evidence showing a high prevalence of chest pain and arrhythmia 2 . Additionally, studies have not only found a significant decline in the aerobic condition of these individuals 3 but also identified an increased risk for chronotropic incompetence, a condition defined as an insufficient increase in heart rate to meet metabolic demands 4 . Such cardiac manifestations can lead to exercise intolerance, a deterioration in quality of life, and an increased risk of cardiovascular events and mortality, underscoring the need for a deeper understanding of cardiac involvement in long COVID.…”
mentioning
confidence: 99%